2021
DOI: 10.1111/febs.15819
|View full text |Cite
|
Sign up to set email alerts
|

The expression of P2Y6 receptor promotes the quality of mucus in colitic mice

Abstract: In the intestine, mucins are expressed and secreted by goblet cells and enterocytes in a constitutive manner and in response to secretagogues to form a protective mucus layer. This protective barrier is often lost in inflammatory bowel disease (IBD). Interestingly, extracellular nucleotides, through P2Y receptors, were identified as mucin secretagogues in mucinous epithelia. These nucleotides are found in the intestine’s extracellular milieu under basal conditions and in higher concentrations in pathologies su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Increasing evidence show that P2Y receptor is involved in the pathogenesis of inflammatory diseases and tumors 14 . While the P2Y1, P2Y2 and P2Y6 of P2Y receptor involved in the development of UC has been described 12 , 26 - 27 , the role of P2RY13 in UC has never been investigated. P2RY13 is one of the important members of the P2Y receptor family and is synthesized by 354 amino acid codes.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence show that P2Y receptor is involved in the pathogenesis of inflammatory diseases and tumors 14 . While the P2Y1, P2Y2 and P2Y6 of P2Y receptor involved in the development of UC has been described 12 , 26 - 27 , the role of P2RY13 in UC has never been investigated. P2RY13 is one of the important members of the P2Y receptor family and is synthesized by 354 amino acid codes.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that ENTPDase8 can similarly reduce intestinal inflammation by limiting P2Y6 receptor activation [ 36 ]. But additional studies on the P2Y6 receptor have found that P2Y6 − / − mice are more susceptible to DSS-induced inflammation than WT mice, and P2Y6 deficiency can affect the secretion of a protective mucus layer in the gut or lead to abnormal activation of Th17/Th1 lymphocytes [ 37 , 38 ]. This change may be related to the alteration of intestinal microbiota after P2 receptor deletion, and high-affinity IgA may maintain the balance of intestinal ecology by limiting the growth of certain bacteria.…”
Section: Possible Targets Of Gut Microbiota Involved In Purinergic Si...mentioning
confidence: 99%
“…Mice lacking P2ry6 are more susceptible to colitis induced by dextran sodium sulphate (DSS) via ulcer promotion, suggesting a protective role in IBD. 12 …”
Section: Introductionmentioning
confidence: 99%
“…The P2 receptor family is widely distributed and expressed in the enteric nervous system and epithelial cells, suggesting that it has a key role in IBD pathogenesis. Mice lacking P2ry6 are more susceptible to colitis induced by dextran sodium sulphate (DSS) via ulcer promotion, suggesting a protective role in IBD 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation